Transmedia Storytelling in Spanish Fiction TV: Antena 3 Case Study - Mayor Mayor, Francesc (CIC. Cuadernos de Información y Comunicación, 2014)
The current article aims to get a closer look at the phenomenon that is the fictional expansion from TV series produced in Spain to the other cultural products that surround them. This study will focus on a TV station, Antena 3, and on four Spanish TV series produced for the aforementioned station: Compañeros, Los protegidos, El Barco, and Hispania. The primary objectives in this study are to confirm that transmedia storytelling is taking its first steps in Spain, to describe transmedia strategies in a TV station in some of its products, and to compare such strategies with those of other North American series. Finally, why this TV station was chosen will be justified during the analysis herein, and strengths and weaknesses of this decision will be discussed.